2019
DOI: 10.1016/j.jaci.2018.12.1022
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of RGMb inhibits allergen-induced airways disease

Abstract: Background: Allergic asthma causes morbidity in many subjects, and novel precision-directed treatments would be valuable. Objective: We sought to examine the role of a novel innate molecule, repulsive guidance molecule b (RGMb), in murine models of allergic asthma. Methods: In models of allergic asthma using ovalbumin or cockroach allergen, mice were treated with anti-RGMb or control mAb and examined for airway inflammation and airway hyperreactivity (AHR), a cardinal feature of asthma. The mechanisms by which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Targeting PD-L2 using its ligand, repulsive guidance molecule b (RGMb), was proposed a therapeutic approach for allergic asthma [24]. However, it has been recently revealed that the anti-allergic effect of RGMb in a mouse model of asthma is independent of PD-L2 interaction further confirmed in PD-L2 deficient mice sensitized to OVA which may require to be validated in protease allergen models such as HDM [25]. In addition, Minkyoung et al have reported a complex mechanism in which protease-fibrinogen cleavage products-TLR4-mast cell-IL-13 axis favors development of pro-allergic/asthmatic PD-L2 + DCs in mice [26].…”
Section: Plos Onementioning
confidence: 99%
“…Targeting PD-L2 using its ligand, repulsive guidance molecule b (RGMb), was proposed a therapeutic approach for allergic asthma [24]. However, it has been recently revealed that the anti-allergic effect of RGMb in a mouse model of asthma is independent of PD-L2 interaction further confirmed in PD-L2 deficient mice sensitized to OVA which may require to be validated in protease allergen models such as HDM [25]. In addition, Minkyoung et al have reported a complex mechanism in which protease-fibrinogen cleavage products-TLR4-mast cell-IL-13 axis favors development of pro-allergic/asthmatic PD-L2 + DCs in mice [26].…”
Section: Plos Onementioning
confidence: 99%
“…This distinction could be linked to the different interactions between PD-1 and PD-L2. Considering serious immune-related TEAEs as a limiting factor in immunotherapy, Envafolimab appears more suitable for high-risk groups like elderly patients with interstitial lung diseases ( Xiao et al, 2014 ; Yu et al, 2019 ; Chen et al, 2022 ). Unlike pembrolizumab and other approved PD-1/PD-L1 antibodies administered intravenously-potentially leading to life-threatening infusion reactions-Envafolimab is given subcutaneously without such reactions ( Kwok et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when the airway barrier is stimulated by external stimuli such as cold air, house dust mites and pathogens, airway epithelium and bronchial epithelium can express pattern recognition receptors and secrete various factors to activate dendritic cells, innate and acquired immunity [16,24,25]. In our previous study, BECs might act as antigenpresenting cells and involve with airway epithelium inflammation via the expression of cytokines and cytokine receptors.…”
Section: Ethics Approval and Consent To Participatementioning
confidence: 94%